2020
DOI: 10.3390/su12083478
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Response Patterns of Tourist Flow under Real-Time Tourist Flow Diversion Scheme

Abstract: This paper excavates tourist decision-making mechanism under the real-time tourist flow diversion scheme (RTFDS) and evaluates the tourist flow diversion effect of RTFDS. To meet the objectives, the stated preference survey and tourist flow survey of the Summer Palace were implemented. The tourist behavior adjustment model and tourist flow diversion simulation model were established. The results show that: (a) For core tourist spots, 66.5% and 16.5% of tourists will choose “behavior adjustment” and “no longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Analysis of behavioral differences resulting from changes in factors, policy implementation, and increases or decreases in alternatives. In addition, the implementation effects of different measures and scenarios can be predicted in the early stage [10].…”
Section: Modeling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of behavioral differences resulting from changes in factors, policy implementation, and increases or decreases in alternatives. In addition, the implementation effects of different measures and scenarios can be predicted in the early stage [10].…”
Section: Modeling Methodsmentioning
confidence: 99%
“…), tour characteristics (number of visitors, frequency of visits, etc. ), information obtained and environmental and psychological factors [10,23,33,34]. Shailes et al [35] showed that attitude, group size and visit frequency were the main factors that influenced holiday travel behavior.…”
Section: Travel Behavior During Holidaysmentioning
confidence: 99%
“…Hence, pedestrians at a higher demand level are bound to adopt the travel decision-making behavior in the face of environmental changes to maintain the higher travel experience level. When the environment changes, pedestrians change or adjust the original travel plan to adapt to the travel demand in the new environment; in this process, the decisionmaking behavior occurs [15][16][17]. The route decision-making behavior is one of the travel decision-making behaviors.…”
Section: Travel Decision-making Behaviormentioning
confidence: 99%
“…Acampa, G. et al similarly used social network analysis to assess the importance of tourism flow management in enhancing tourism attractiveness, and based on this, proposed a new measurement index that can effectively reflect the level of tourist dissatisfaction [12]. Yang, G. et al in order to better propose a tourism diversion real-time scheme, the tourism behavior adjustment model was used to extract the behavioral patterns of tourists under different conditions, and a simulation model of tourism flow diversion based on dynamic adjustment was established [13]. In addition to real-time tourist diversion, the prediction of tourist flow is also an effective perspective to improve the tourist experience.…”
Section: Introductionmentioning
confidence: 99%